2017
DOI: 10.1021/acs.langmuir.6b04455
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching of Azobenzene-Based Reverse Micelles above and at Subzero Temperatures As Studied by NMR and Molecular Dynamics Simulations

Abstract: We designed and studied the structure, dynamics, and photochemistry of photoswitchable reverse micelles (RMs) composed of azobenzene-containing ammonium amphiphile 1 and water in chloroform at room and subzero temperatures by NMR spectroscopy and molecular dynamics simulations. The NMR and diffusion coefficient analyses showed that micelles containing either the E or Z configuration of 1 are stable at room temperature. Depending on the water-to-surfactant molar ratio, the size of the RMs remains unchanged or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…However, through the azobenzene fragment incorporated into the hydrophobic tail, the above-mentioned processes can be remotely controlled via light stimulus. For instance, micelle formation, foam stability and surface forces, manipulation of complex fluids, motion of microparticles, and control of interfacial movements are now becoming light-triggered in modern nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…However, through the azobenzene fragment incorporated into the hydrophobic tail, the above-mentioned processes can be remotely controlled via light stimulus. For instance, micelle formation, foam stability and surface forces, manipulation of complex fluids, motion of microparticles, and control of interfacial movements are now becoming light-triggered in modern nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…The present large scale of ladder architecture indicated that the assembly of the polymeric molecules might also exhibit π−π attractions between end groups (vinyl and styryl) along the longitudinal axis of the polymers and van der Waals interactions between the neighboring polymeric backbones [10], as shown in Figure 2c,d. Interestingly single-stranded P2 (Figure 3) showed micelles morphology with size mostly in the range of 50-80 nm, which is similar to that of azobenzene-based micelles [39]. In the spheres formed by self-assembly, the size observed in Dynamic Light Scattering (DLS) increased and was in the range of 60-120 nm, which might be attributed to the solvation of polymer in solution.…”
Section: Morphology Of Ordered Ladder Architecturementioning
confidence: 58%
“…UV/Vis spectroscopy showed that E-1•Zn 2+ possessed an absorption maximum at 360 nm, which is in accordance with previously synthesized 4,4'-dialkoxyazobenzenes. [35] Irradiation with UV light at 365 nm for 15 min converted 1•Zn 2+ to the Z-isomer,which possessed two bands at l max 320 and 450 nm. To accurately quantify the ratio of E-1 to Z-1,t he 1 (Figure 2d,i ).…”
mentioning
confidence: 99%
“…[36] Figure 3a shows this shift as increasing amounts of E-orZ-1•Zn 2+ is titrated into abuffered solution Scheme 1. Synthesis of the photoresponsive amphiphile 1 and control molecule C. [35] Angewandte Chemie Zuschriften containing the HPNPP substrate.T he measured CACfor E-1•Zn 2+ was determined to be 20 mm,w hile the CACo fZ-1•Zn 2+ was determined to be 60 mm.I ti sn otable that the control molecule C,w hich has 6f ewer carbons in its hydrophobic chain than 1 was also studied and was found not to form significant aggregates under the conditions examined (up to 200 mm).…”
mentioning
confidence: 99%